Characteristics and outcomes of pediatric testicular yolk Sac tumor - Li, Maoxian; Wang, Jinkui; Wang, Jianyu; Zhang, Deying; Hua, Yi; Liu, Feng; Lu, Peng; Liu, Junhong; Liu, Xing; Lin, Tao; Wei, Guanghui; He, Dawei (Frontiers in Pediatrics, 2022)
Purpose Pediatric testicular yolk sac tumor is a rare malignant germ cell tumor and there is a lack of large clinical studies. The purpose of this study is to summarize the clinical characteristics of pediatric testicular yolk tumor and evaluate the prognostic factors. Materials and methods The medical records of children with testicular yolk sac tumor in one pediatric medical centre in China from January 2005 to January 2021 were retrospectively investigated. Data regarding clinical characteristics, treatment and prognosis were collected. Results A total of 109 patients with a median diagnosed age of 18 months (range 2–69) were included in this study; of them 100 were diagnosed as stage I, 6 as stage II and 3 as stage IV. All patients underwent radical orchiectomy, and 61 of them underwent postoperative chemotherapy. The mean follow-up time was 61.3 months (range 3–259), during that time, 8 patients experienced relapse. The five-year overall survival was 90.6% (95% CI 84.6%–96.7%). Univariate Cox regression analysis showed that disease stage, relapse, maximum tumor diameter, and alpha-fetoprotein returning to normal within 2 months postoperatively were risk factors for survival (HRs of 25.43, 26.43, 1.48 and 0.08, respectively, p < 0.05). Multivariate Cox regression analysis suggested that higher disease stage and relapse were independent adverse factors for survival (HRs of 148.30 and 94.58, respectively, p < 0.05). Conclusions The prognosis of pediatric testicular yolk sac tumor is generally excellent. A higher disease stage and the occurrence of relapse could predict a poor prognosis. The individualized management of children with testicular yolk sac tumor according to risk classification is feasible.